2020
DOI: 10.1038/s41598-020-75165-8
|View full text |Cite
|
Sign up to set email alerts
|

Topological transitions in an oscillatory driven liquid crystal cell

Abstract: Matter under different equilibrium conditions of pressure and temperature exhibits different states such as solid, liquid, gas, and plasma. Exotic states of matter, such as Bose–Einstein condensates, superfluidity, chiral magnets, superconductivity, and liquid crystalline blue phases are observed in thermodynamic equilibrium. Rather than being a result of an aggregation of matter, their emergence is due to a change of a topological state of the system. These topological states can persist out of thermodynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Clerc et al have justified the grid pattern formation as a consequence of a Carr-Helfrich mechanism. [46] However, the presence of the pillars, present in this experimental system, modifies this scenario. [27] In fact, as the reorientation proceeds starting from the pillars, the pillars act as attraction sites, or pinning sites, of umbilical defects with projected charge +1.…”
Section: Methodsmentioning
confidence: 91%
“…Clerc et al have justified the grid pattern formation as a consequence of a Carr-Helfrich mechanism. [46] However, the presence of the pillars, present in this experimental system, modifies this scenario. [27] In fact, as the reorientation proceeds starting from the pillars, the pillars act as attraction sites, or pinning sites, of umbilical defects with projected charge +1.…”
Section: Methodsmentioning
confidence: 91%
“…32,33 These chiral nematic LCs can transition from a state with no vortices to a stable vortex state when subjected to an oscillatory applied field of low frequency. 34 Additional work with this material demonstrated that traveling waves can control the orientation of the director profile. 35 The majority of these works discussed above were in systems with a spatially uniform electric field in the typical sandwich geometry.…”
Section: Introductionmentioning
confidence: 98%
“…Due to the conservation of the global topological charge, vortices are created and annihilated by pairs with opposite charges 6,8 . However, when considering inhomogeneities such as thermal gradients, 9 mechanical defects, 10 ionic impurities 11 or low-frequency voltages, 12 the previous dynamical behavior changes, in a way that vortices can be trapped.…”
Section: Introductionmentioning
confidence: 99%